smansapala123@yahoo.com - Ajrianto Ajrianto Ajrianto (UNIVERSITAS BENGKULU, 2016)
This study aims to decrypt: 1) Strategic planning of school work program to improve the quality of education in school. 2) Implementation of the work plan in school, 3) evaluation andsupervision of school work plan. Research conducted using qualitative description. Activity was collected using the techniques of observation, interviews, and documentation. Based on research, it can be concluded in school has conducted planning school work optimally in terms of both thesteps of planning work program, the implementation of the work plan of the school as well as the evaluation and supervision of school work plan to be comprehensive, objective, responsible and sustainable, as well as disseminated to all teachers and education personnel.Keywords: strategy, principal, quality education